STUDI ERODIBILITAS TANAH PADA LAHAN BEKAS PENAMBANGAN TANAH (GALIAN C) DI KELURAHAN SEDAU KECAMATAN SINGKAWANG SELATAN KOTA SINGKAWANG - Fahrul Rozi; Saifudin Saifudin; Junaidi Junaidi (Perkebunan dan Lahan Tropika, 2022)
This study aimed to assess and compare the soil erodibility (K) in the former mining land (quarry C) with different degree of slope on the hills in the Village area Sedau. Analysis of the data used deskriktif analysis. Ie using paired T test, soil sampling was carried out with a free grid method in soil samples taken in the form of intact or undisturbed and disturbed soil samples. Observation point includes 3 levels of the slope of the former mining land (quarry C), the slope of the land 250, 300 land slope, and the slope of the land 450. where in each class a different slope samples taken 5 points of observation with a depth of 0-10 cm layer. The measurement includes the observation variables, (a) texture, (b) permeability, (c) organic materials, (d) size of the soil structure. The average value of soil erodibility obtained classified into low soil erodibility class, with range values ranged erodibility (0.11 to 0.20) which erodibility values contained in the slope class 250 value 0,18 and in the slope class 300 have the value of 0.15 , while the slope for class 450 with a value of 0.15.